2000
DOI: 10.2174/1381612003400597
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Therapy for Cancer

Abstract: Modulation of immune responses by the use of recombinant cytokines or cytokine genes is one of the strategies for cancer therapy. Although host immune responses are complex and many kinds of cells are involved, crucial steps for enhancing anti-tumor responses can be induced by a single or a few cytokines administered. However, cytokines may induce toxic reactions or produce no substantial effects, when the concentration is inappropriate. Administration of recombinant cytokine(s) has advantages in controlling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 114 publications
3
29
0
Order By: Relevance
“…An increased level of IL-2 is involved in efficient cellular immune function (31). Previous studies have shown that a locally-secreted high level of IL-2 generates fewer side effects compared with a systemically administered high dose of IL-2 (31,32). In the present study, the low level of IL-2 present during the formation of liver lesions was significantly increased during treatment with LUT.…”
Section: Discussionsupporting
confidence: 53%
“…An increased level of IL-2 is involved in efficient cellular immune function (31). Previous studies have shown that a locally-secreted high level of IL-2 generates fewer side effects compared with a systemically administered high dose of IL-2 (31,32). In the present study, the low level of IL-2 present during the formation of liver lesions was significantly increased during treatment with LUT.…”
Section: Discussionsupporting
confidence: 53%
“…The mice that had rejected IL-21-producing clones became resistant to Colon 26 cells that were subsequently inoculated, but about a half of them developed irrelevant RL male-1 tumors (Table 1). When the mice were treated with anti-asialo GM 1 ), a half of the mice rejected the mixed tumor cells after forming small tumor masses (Table 1). All the mice that received 5 Â 10 5 parent cells as a control developed tumors progressively.…”
Section: Establishment Of Il-21-expressing Cellsmentioning
confidence: 99%
“…1 Cytokines released from T-helper type-1 cells but not type-2 cells have more effectively produced antitumor activities in a number of experimental animal models because the cytokines enhance cell-mediated immunity.…”
mentioning
confidence: 99%
“…38 Although the exact role of types 1 and 2 responses in human tumor immunology remains to be defined, a CTL type of immune response seems to be associated with Th1 cytokines, whereas Th2 cytokines are more often associated with antibody production. 39 It is tempting to speculate that intratumoral treatment with Vero -IL -2 caused a local shift toward a humoral -type rather than a cellular-type immune response, thereby decreasing the effective overall antitumor immunity, and thus explaining the disappointing clinical activity of TG2001.…”
Section: Discussionmentioning
confidence: 99%